In Vivo Metabolic Tracing Demonstrates the Site‐Specific Contribution of Hepatic Ethanol Metabolism to Histone Acetylation. (16th August 2018) - Kriss, Crystina L.; Gregory‐Lott, Emily; Storey, Aaron J.; Tackett, Alan J.; Wahls, Wayne P.; Stevens, Stanley M.
Abstract : Background: Epigenetic dysregulation through ethanol (EtOH)‐induced changes in DNA methylation and histone modifications has been implicated in several alcohol‐related disorders such as alcoholic liver disease. EtOH metabolism in the liver results in the formation of acetate, a metabolite that can be converted to acetyl‐CoA, which can then be used by histone acetyltransferases to acetylate lysine residues. EtOH metabolism in the liver can also indirectly influence lysine acetylation through NAD + ‐dependent sirtuin activity that is altered due to increases in NADH. As a proof‐of‐concept study to determine the direct influence of hepatic EtOH metabolism on histone acetylation changes, we used heavy‐labeled EtOH ( 13 C2 ) and mass spectrometry (MS) to site specifically characterize lysine acetylation on histone proteins. Methods: Eight‐week‐old male C57BL/6J mice were gavaged using a bolus dose of either 13 C2 ‐labeled EtOH (5 g/kg) or maltose dextrin. Blood and livers were collected at 0, 4, and 24 hours followed by histone protein enrichment and derivatization using acid extraction and propionylation, respectively. Metabolic tracing and relative quantitation of acetylated histone proteins were performed using a hybrid quadrupole‐orbitrap mass spectrometer. Data were analyzed using MaxQuant, Xcalibur Qual Browser, and the Bioconductor package "mzR." The contribution of EtOH to histone acetylation was quantified using the change in relative abundance of stable isotope incorporation in acetylated peptides detected by MS. Results: Data show significant incorporation of the EtOH‐derived 13 C2 ‐label into N‐terminal lysine acetylation sites on histones H3 and H4 after 4 hours, with rapid turnover of labeled histone acetylation sites and return to endogenous levels at 24 hours postgavage. Moreover, site‐specific selectivity was observed in regard to label incorporation into certain lysine acetylation sites as determined by tandem mass spectrometry and comparison to isotope simulations. Conclusions: These data provide the first quantitative evidence of how hepatic EtOH metabolism directly influences histone lysine acetylation in a site‐specific manner and may influence EtOH‐induced gene expression through these transcriptionally activating chromatin marks. Abstract : Hepatic ethanol metabolism results in the production of acetyl‐CoA from acetate, which subsequently can be utilized for histone acetylation by histone acetyltransferases (HATs). This study describes a novel in vivo metabolic tracing approach using high‐resolution mass spectrometry that allows for site‐specific identification and quantification of histone acetylation influenced directly by ethanol metabolism. Using stable isotope‐labeled ethanol in an acute exposure model of alcohol exposure in mice, we identified multiple histone acetylation sites that demonstrate significant incorporation of the ethanol‐derived label.